2022
DOI: 10.3389/fcimb.2022.978440
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing anti-HCoV-OC43 immunity influences the durability and cross-reactivity of humoral response to SARS-CoV-2 vaccination

Abstract: PurposeThis study was conducted in order to properly understand whether prior seasonal human coronavirus (HCoV) immunity could impact the potential cross-reactivity of humoral responses induced by SARS-CoV-2 vaccine, thereby devising universal coronavirus vaccines for future outbreaks.MethodsWe performed enzyme-linked immunosorbent assay (ELISA) to quantify the immunoglobulin G (IgG) antibody levels to spike (S) protein and S1 subunit of HCoVs (HCoV-OC43, HCoV-HKU1, HCoV-NL63, and HCoV-229E), and ELISA [anti-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Cross-reactivity could be related to previous immunization against common cold coronavirus infections. Although we did not find a relationship between in vitro T-cell reactivity against SARS-CoV-2 peptides in healthy controls and T-cell response against HCoV-229E, we cannot rule out the possibility that proliferation against other common coronaviruses such as HCoV-OC43, HCoV-NL63, HCoV-HKU1 may exist in controls ( 18 , 23 ). Nevertheless, despite cross-reactivity, proliferative response had a good ability to discriminate between individuals with resolved infection and unexposed individuals.…”
Section: Discussionmentioning
confidence: 64%
“…Cross-reactivity could be related to previous immunization against common cold coronavirus infections. Although we did not find a relationship between in vitro T-cell reactivity against SARS-CoV-2 peptides in healthy controls and T-cell response against HCoV-229E, we cannot rule out the possibility that proliferation against other common coronaviruses such as HCoV-OC43, HCoV-NL63, HCoV-HKU1 may exist in controls ( 18 , 23 ). Nevertheless, despite cross-reactivity, proliferative response had a good ability to discriminate between individuals with resolved infection and unexposed individuals.…”
Section: Discussionmentioning
confidence: 64%
“…Despite an overall low response, NtAb titers to BA.5 varied over three orders of magnitude. This might reflect the inclusion of subjects with an undiagnosed prior SARS-CoV-2 infection and/or higher cross-reactivity due to prior exposure to seasonal human coronaviruses [31]. The latter could explain the positive correlation between BA.5 NtAb titers and patient age detected in our case file, but this is a hypothesis that needs to be confirmed on a larger number of patients.…”
Section: Discussionmentioning
confidence: 81%
“…Che and colleagues [ 45 ] found that sera from SARS-CoV-1 showed a several fold increase in antibody titers against HCoV-229E and HCoV-OC43 compared to controls. Hu and colleagues [ 47 ] reported that preexisting antibodies to HCoV-OC43 in healthy people were positively correlated with an immune response against the receptor binding domain (RBD) found in the S protein of SARS-CoV-2 and neutralization antibodies to SARS-CoV-2 in people who had been vaccinated against SARS-CoV-2. The alignment of these coronaviruses S protein sequences suggested possible cross-reactive immunity against peptides 319 -RVQPTESTIVRFP, 332 -ITNLCPFGEVF, 358 -ISNCVADYSVLYNSA, 374 -FSTFKCYGVSPT, 388 -NDLCFTNVYADSFVIRG, 407 -VRQIAP, 429 -FTGCVIAW, 450 -NYLYRLFR, 470 -TEIYQAGS, 504 -GYQPYRVVVLSFELL, and 535 -KNKCVNF, some of which (e.g., 407 -VRQIAP) had been previously identified as SARS-CoV-2 spike protein S1 subunit (S1) linear B cell epitopes [ 48 , 49 ].…”
Section: Evidence Of Cross-reactivity Towards Hcov Mers-cov Sars-cov-...mentioning
confidence: 99%
“…Unsurprisingly, due to the sequence identities or similarities of proteins between the different coronaviruses, the literature reports a large number of cases of cross-reactions between different coronaviruses and SARS-CoV-2, and it is broadly distributed across the viral proteome, including the spike protein with recognition of the spike RBD [ 47 , 50 , 52 , 57 , 132 , 133 , 134 ]. What appears less clearly is the frequency of people who had probably never been exposed to SARS-CoV-2 and who have cross-immunity to SARS-CoV-2 pre-existing their infection or vaccination.…”
Section: Prepandemic Cross Immunity To Sars-cov-2mentioning
confidence: 99%